2019
DOI: 10.3390/geriatrics4010008
|View full text |Cite
|
Sign up to set email alerts
|

DEMMI Scores, Length of Stay, and 30-Day Readmission of Acute Geriatric Patients in Denmark: A Cross-Sectional Observational Study with Longitudinal Follow-Up

Abstract: The aims of this study are to describe the mobility of acute geriatric patients, the length of stay, and to characterise patients who were readmitted within 30 days based on the De Morton Mobility Index (DEMMI). A cross-sectional observational study with longitudinal follow-up was conducted in the period from 1 March 2016 to 31 August 2016. Inclusion criteria were acute geriatric patients hospitalised for a minimum of 24 h. Of the 418 patients hospitalised during the study period, 246 (59%) participated in thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 30 publications
1
7
0
1
Order By: Relevance
“…We will perform subgroup analysis for age groups <65 years vs ≥65 years, initial performance in physical activity (DEMMI≤40 vs DEMMI>40), and prehospital mobility (no mobility aid vs prehospital use of mobility aid) because previous studies showed that older age categories had significantly lower mean DEMMI scores, 46 and lower Barthel index and use of mobility aids or being bedridden was associated with lower DEMMI scores. 42 Any deviation from the original statistical plan will be described and justified in the final trial report. There is no interim analysis planned, that is, there are no stopping rules on the individual or trial level.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We will perform subgroup analysis for age groups <65 years vs ≥65 years, initial performance in physical activity (DEMMI≤40 vs DEMMI>40), and prehospital mobility (no mobility aid vs prehospital use of mobility aid) because previous studies showed that older age categories had significantly lower mean DEMMI scores, 46 and lower Barthel index and use of mobility aids or being bedridden was associated with lower DEMMI scores. 42 Any deviation from the original statistical plan will be described and justified in the final trial report. There is no interim analysis planned, that is, there are no stopping rules on the individual or trial level.…”
Section: Discussionmentioning
confidence: 99%
“…Acute older adult patients with a DEMMI score below 41 score points had significantly lower Barthel index (38% vs 79%), used more mobility aids, were more bedridden, longer hospitalised and were more often discharged to rehabilitation compared with those with a higher DEMMI score. 42 No association was found for gender, age, weight, body mass index, Charlson comorbidity index or handgrip strength. 42 Trained personnel is able to complete the DEMMI in no more than 10 min.…”
Section: Open Accessmentioning
confidence: 93%
See 1 more Smart Citation
“…28 Completion of a TUG may be clinically inappropriate in some injuries; however, the DEMMI is an alternative tool for patients with lower functional capacity, which has been validated for inpatient use and associated with hospital LOS and 30-day readmission. 9,29 Further understanding of clinician perspectives is required to ascertain the poor completion of physical outcome measures. These results further highlight the limited assessment provided to 'high'-risk fallers and strengthens the argument for implementation of a fall-specific pathway in the ED.…”
Section: Physical Assessmentmentioning
confidence: 99%
“…1,2,3 Lama rawat pasien geriatri dipengaruhi oleh beberapa faktor, antara lain diagnosis utama dan komorbiditas, status nutrisi, status fungsional, derajat beratnya penyakit, keberadaan berbagai dukungan yang dibutuhkan, serta beberapa faktor psikososial. [4][5][6][7][8] Bila pasien geriatri dirawat inap karena infeksi, jenis mikroorganisme dan ada tidaknya sepsis menjadi penting.…”
Section: Pendahuluanunclassified